2017
DOI: 10.1007/s11340-017-0298-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Diffraction Residual Strain Measurements of Molybdenum Carbide-Based Solid Oxide Fuel Cell Anode Layers with Metal Oxides on Hastelloy X

Abstract: Thermal spray deposition processes impart residual stress in layered Solid Oxide Fuel Cells (SOFC) materials and hence influence the durability and efficiency of the cell. The current study which is the first of its kind in published literature, reports results on using a neutron diffraction technique, to non-destructively evaluate the through thickness strain measurement in plasma sprayed (as-sprayed) anode layer coatings on a Hastelloy®X substrate. Through thickness neutron diffraction residual strain measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 51 publications
(103 reference statements)
1
44
0
Order By: Relevance
“…As observed through recent investigation ( [13], Appendix A.1), neutron diffraction residual stress values for the same coating-substrate specimen (Mo-Mo2C/Al2O3 coating on Hastelloy ® X substrate), it was observed that the difference between average residual stress (102 MPa in substrate, 41 MPa in substrate) is about 61 MPa, with about 150 MPa average stress mis-match at the interface. It can be observed that the through thickness residual strain (or stress) profile is complex and ideally it could be superimposed on the compression stress field [13]. However, such experimental data of residual strain (or stress) is not three dimensional and such superimpositions is not trivial for a three-dimensional stress field during the compression test.…”
Section: Comparison Of Coated To Uncoated Disc Facessupporting
confidence: 61%
See 4 more Smart Citations
“…As observed through recent investigation ( [13], Appendix A.1), neutron diffraction residual stress values for the same coating-substrate specimen (Mo-Mo2C/Al2O3 coating on Hastelloy ® X substrate), it was observed that the difference between average residual stress (102 MPa in substrate, 41 MPa in substrate) is about 61 MPa, with about 150 MPa average stress mis-match at the interface. It can be observed that the through thickness residual strain (or stress) profile is complex and ideally it could be superimposed on the compression stress field [13]. However, such experimental data of residual strain (or stress) is not three dimensional and such superimpositions is not trivial for a three-dimensional stress field during the compression test.…”
Section: Comparison Of Coated To Uncoated Disc Facessupporting
confidence: 61%
“…The coated disc specimen was sourced from work completed previous to the investigation [13,32], as shown in Fig. 3 was assumed as 0.30 (Molybdenum Poisson's ratio) and for the substrate ( s ν ) was presumed to be 0.32 [33].…”
Section: Coating and Disc Substrate Materialsmentioning
confidence: 99%
See 3 more Smart Citations